Combine Effect of Vitamin C and venlafaxine on the Amino Acid Content of Saccharomyces cerevisiae - Özer, Dursun; Karataş, Fikret; Çakmak, Meltem; SAYDAM, Sinan (European Journal of Applied Sciences, 2021)
In this study, Saccharomyces cerevisiae (NRLLY-12632) was grown in YPD medium containing different concentrations of venlafaxine, (RS)-1-[2-dimethylamino-1-(4-methoxyphenyl)-ethyl] cyclohexanol. To counteract the effect of venlafaxine, vitamin C were added to the growth medium of S. cerevisiae, and amino acids content were investigated by HPLC. It was observed that, the amount of amino acids in S. cerevisiae grown in YPD medium, containing 100, 200, 300, 400 and 500 ppm venlafaxine were compared with the control, the amounts of alanine, arginine, asparagine, aspartic acid, cysteine, glycine, histidine, isoleucine, leucine, lysine, phenylalanine, proline, threonine, tyrosine and valine increased (p<0.05), glutamic acid, glutamine, methionine, serine and tryptophan levels were decreased p<0.05). With the addition of vitamin C to the growth medium containing venlafaxine, all the amino acids concentrations get close to the control group. From these findings, it can be said that the negative effect of venlafaxine on S. cerevisiae is reduced by the addition of vitamin C to the medium.